EVALUATION OF CERTAIN INSECTICIDE MOLECULES AGAINST MITE, Polyphagotarsonemus latus Banks ON CAPSICUM - P. VIJAYALAKSHMI, T.V.K. SINGH, S.B. VEMURI, R.V.S.K. REDDY AND N.B. BHARATHI (The Journal of Research ANGRAU, 2015)
Field and poly house experiments were conducted to evaluate the new insecticides for the management ofmite, Polyphagotarsonemus latus Banks on capsicum. Among the seven insecticides, mean of two seasons underfield conditions reveal that, post count population was lower with spiromesifen (0.62 mites leaf-1) followed bydiafenthiuron (4.08 mites leaf-1), triazophos (5.73 mites leaf-1) and thiamethoxam (9.43 mites leaf-1) which weresuperior over rest of the treatments and untreated check (17.60 mites leaf-1). Under poly house condition, populationwas less with spiromesifen (0.06 mites leaf-1) followed by diafenthiuron (2.21 mites leaf-1), triazophos (3.68 mites leaf-1) and thiamethoxam (5.30 mites leaf-1) which were superior over untreated check (11.33).Comparision of efficacy ofinsecticides, there was significant difference in percent reduction of population over untreated check after each spray.The percent reduction and mortality in mite population were high in poly house (spiromesifen, flubendiamide andspinosad) compared to open field.